Integrated natural resource management in sustainable urban context - Renata Valente; Louise Anna Mozingo; Roberto Bosco; Savino Giacobbe (Agathón)
Based on national and international references, the research evaluates the integration of low-impact ecological interventions within the perimeters of Renewable Energy Communities in the Metropolitan City of Naples, with High Schools serving as hubs. The paper estimates a pilot case study within the Municipality of Giugliano in Campania (IT) for environmental solutions with integrated and shared management of energy, vegetation, and stormwater through simulations and performance indicators. The results highlight the effectiveness of a systemic approach to the design of public spaces in terms of energy savings and greenhouse gas emissions, going beyond the quantitative conception of public facilities. The proposed flexible tool supports local administrations to encourage the adoption of virtuous sustainable behaviours.